2009
DOI: 10.1021/jf802642d
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Canadian Cigarettes Using Multi-Stable Isotope Analysis by Gas Chromatography−Isotope Ratio Mass Spectrometry

Abstract: A reliable method for measuring (15)N/(14)N and (2)H/(1)H ratios of nicotine in cigarette tobacco has been developed. It involves a simple procedure for extracting nicotine from tobacco using methanol. The extract is directly analyzed on a gas chromatography isotope ratio mass spectrometer (GC-IRMS). The method is reproducible with 4% RSD for delta(2)H and delta(15)N. Brand name cigarettes manufactured in Canada (N = 47) and in China (N = 23) have been analyzed. The results show that nicotine from Canadian cig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…One hundred percentage methanol on thermomixer (300 rpm) at 60°C for 30 min was found to be the most effective method for nicotine extraction from all types of tobacco samples. Moreover, Binette et al [15] have also recently reported the extraction of nicotine from cigarette by using simply methanol under 4 h of sonication process. T8, B1, N4, N10, and G2 samples were used in this study and showed maximum extraction efficiency.…”
Section: Extraction Methodology and Extraction Efficiencymentioning
confidence: 99%
“…One hundred percentage methanol on thermomixer (300 rpm) at 60°C for 30 min was found to be the most effective method for nicotine extraction from all types of tobacco samples. Moreover, Binette et al [15] have also recently reported the extraction of nicotine from cigarette by using simply methanol under 4 h of sonication process. T8, B1, N4, N10, and G2 samples were used in this study and showed maximum extraction efficiency.…”
Section: Extraction Methodology and Extraction Efficiencymentioning
confidence: 99%
“…In 1997, Jamin and colleagues [25] published a paper on the multi-element and multi-site isotopic analysis of purified nicotine extracted from tobacco leaves, concluding that the carbon and nitrogen isotopic composition ( 13 C/ 12 C, 15 N/ 14 N) and the site-specific deuterium content of nicotine can provide useful information on the geographical origin of tobacco. Similarly, Binette and colleagues [30] found that the combination of 2 H/ 1 H and 15 N/ 14 N ratios can be useful for identifying foreign counterfeits of Canadian cigarettes. To date, the elemental composition of tobacco has been investigated mainly to assess the presence of toxic elements that can be inhaled or absorbed through cigarette smoke [21][22][23].…”
Section: Introductionmentioning
confidence: 94%
“…In addition, the literature reports that although the δ 2 H value of Canadian cigarettes is higher than that of Chinese cigarettes, the δ 2 H value was still lower than À163.0‰. 33 It is worth mentioning that the synthetic nicotine of route 6 was determined to be (S)-(À)-nicotine by chirality analysis (Figure S4). This technology would therefore remedy the defect of chiral chromatography in classifying natural from synthetic (S)-(À)-nicotine.…”
Section: Perspective For the Authentication Of Nicotinementioning
confidence: 99%